Sources of astronomical knowledge among Muslims during the Abbasid era (132-656 AH / 750-1258 AD): “Indian and Persian sources as an example” - Abdullah, Hassan; Ibrahim, Musa (Humanities Journal of University of Zakho, 2023)
The study of the sources of astronomical knowledge among Muslims is considered as one of important studies. Because the first sources from which Muslims drew their astronomical knowledge were (Hindi, Persian), in addition to greek sources and pre-Islamic literature and poetry among the Arabs before Islam, as well as the Holy Qur’an and the honorable Sunnah of the Prophet and what is mentioned in it about astronomical phenomena, planets and stars. All pre-mentioned urge Muslims to implement thought in this universe, studying it, diving into its depths and solve its mysteries. It was obvious that the translation movement, especially in the first Abbasid era, had a great role in informing Muslims of the cultural and civilizational heritage of other nations and peoples from different sciences. Astronomy was one of those sciences that the Arabs cared about and increased their interest in it after the advent of Islam. This is due to its connection with some of the legal obligations and rulings, such as prayer times, knowledge of the direction of the qiblah, the crescent of Ramadan, the movement of the sun in the zodiac, the conditions of twilight, and others. Therefore, in our research, we tried to focus on the Indian and Persian sources as a model of those sources for their main role in laying the first foundations for an advanced Islamic astronomy that appeared later in the east and west of the Islamic world, Likewise, we do not forget that astrology had a direct relationship with astronomy, so the interest of ancient peoples in astrology was a great incentive to study, know and care about astronomy, through that internal desire of those nations to look beyond the sky and celestial bodies and their effects and upon which the ancient astronomical observations were based and presented Observational astronomical material is very important for astronomers to pay attention to building observatories, manufacturing astronomical instruments and devices, and the subsequent development at the hands of Muslim astronomers.